Anthropometric characteristics of Australian junior representative rugby league players - Cheng, H. L.; O'Connor, H.; Kay, S.; Cook, R.; Parker, H.; Orr, R. (Journal of Science and Medicine in Sport, 2014)
Objectives: To comprehensively describe anthropometric characteristics of Australian junior elite rugby league players and assess potential anthropometric dissimilarities between players of varying positional groups, ethnicity (Polynesian vs. non-Polynesian) and playing level (junior vs. professional; using published data from Australian professional players). Design: Cross-sectional study. Methods: Height, body mass, eight skinfolds, five girths and two bone breadths were measured with body fat (BF%) and somatotype calculated using population-appropriate equations. Data: mean ± SD. Results: This study recruited 116 junior players. Mean age, mass and BF% were 17 ± 1 y, 87.0 ± 11.6 kg and 14.0 ± 4.6% respectively. Compared to backs, forwards had greater mass (92.6 ± 12.2 vs. 80.9 ± 7.1 kg), skinfolds, girths, femur breadth, BF% (16.1 ± 4.8% vs. 11.8 ± 3.2%) (all p < 0.01), and were more endo- and mesomorphic, but less ectomorphic (all p < 0.001). Compared to other positional groups, props had greater mass, adiposity, calf girth and endomorphy, while adjustables (fullbacks, five-eighths, halfbacks, hookers) had the shortest stature (all p < 0.01). Polynesians exhibited greater height (181.0 ± 5.7 vs. 178.7 ± 6.3 cm), mass (90.6 ± 11.7 vs. 84.7 ± 11.1 kg), arm and calf girths, bone breadths and mesomorphy (7.6 ± 1.2 vs. 6.7 ± 1.1) than non-Polynesians (all p < 0.05). Juniors had lower height, mass, waist and smaller sum of skinfolds than professional players (all p < 0.05). Conclusions: Greater mass, mesomorphy, adiposity and bone size in forwards is desirable for tackling and attacking and may protect against high impact forces sustained in this position. Advantageous anthropometric attributes exhibited in Polynesian players may influence selection into junior elite rugby league teams. Anthropometric data from this study may assist other junior players and coaches with training, dietary modification and position allocation.